Experimentally induced infection with autonomous parvoviruses, minute virus of mice and H-1, in the african multimammate mouse (Mastomys coucha) - Haag, Andreas; Rommelaere, Jean (Comparative medicine, 2000)
To determine whether the multimammate mouse (Mastomys coucha) could be used to evaluate rodent parvovirus-based vectors, neonates were subcutaneously inoculated with minute virus of mice (prototype strain, MVMp) or rat parvovirus H-1. The course of infection with both viruses was similar. Seroconversion occurred within two weeks after virus inoculation, as detected by use of hemagglutination-inhibition assays, and antibody titers remained high for the entire observation period of 12 months. Viral DNA and infective virions were detected in several organs of inoculated animals prior to seroconversion, as measured by use of Southern blotting and plaque assays, respectively. Infective particles subsequently became undetectable, whereas viral DNA imprints persisted in distinct organs for at least nine months. Clinical signs of parvovirus infection appeared around six weeks after virus inoculation, and consisted of hemorrhages, stunted growth, and transient hair color changes. Sudden death occurred in a significant fraction of animals infected with MVMp, but not H-1 virus, at the time of weaning. Alto- gether, MVMp, which is innocuous to its natural host, the mouse, and H-1 virus, which is poorly pathogenic to the rat, appear to be pathogenic for Mastomys coucha.